Influence of group III/IV muscle afferents on small muscle mass exercise performance: a bioenergetics perspective - Broxterman, Ryan M. (J Physiol, 2018)
KEY POINTS: This investigation assessed the influence of group III/IV muscle afferents on small muscle mass exercise performance from a skeletal muscle bioenergetics perspective. Group III/IV muscle afferent feedback was attenuated with lumbar intrathecal fentanyl during intermittent isometric single‐leg knee‐extensor all‐out exercise, while (31)P‐MRS was used to assess skeletal muscle bioenergetics. Attenuation of group III/IV muscle afferent feedback improved exercise performance during the first minute of exercise, due to an increase in total ATP production with no change in the ATP cost of contraction. However, exercise performance was not altered during the remainder of the protocol, despite a sustained increase in total ATP production, due to an exacerbated ATP cost of contraction. These findings reveal that group III/IV muscle afferents directly limit exercise performance during small muscle mass exercise, but, due to their critical role in maintaining skeletal muscle contractile efficiency, with time, the benefit of attenuating the muscle afferents is negated. ABSTRACT: The direct influence of group III/IV muscle afferents on exercise performance remains equivocal. Therefore, all‐out intermittent isometric single‐leg knee‐extensor exercise and phosphorous magnetic resonance spectroscopy ((31)P‐MRS) were utilized to provide a high time resolution assessment of exercise performance and skeletal muscle bioenergetics in control conditions (CTRL) and with the attenuation of group III/IV muscle afferent feedback via lumbar intrathecal fentanyl (FENT). In both conditions, seven recreationally active men performed 60 maximal voluntary quadriceps contractions (MVC; 3 s contraction, 2 s relaxation), while knee‐extensor force and (31)P‐MRS were assessed during each MVC. The cumulative integrated force was significantly greater (8 ± 6%) in FENT than CTRL for the first minute of the all‐out protocol, but was not significantly different for the second to fifth minutes. Total ATP production was significantly greater (16 ± 21%) in FENT than CTRL throughout the all‐out exercise protocol, due to a significantly greater anaerobic ATP production (11 ± 13%) in FENT than CTRL with no significant difference in oxidative ATP production. The ATP cost of contraction was not significantly different between FENT and CTRL for the first minute of the all‐out protocol, but was significantly greater (29 ± 34%) in FENT than in CTRL for the second to fifth minutes. These findings reveal that group III/IV muscle afferents directly limit exercise performance during small muscle mass exercise, but, due to their critical role in maintaining skeletal muscle contractile efficiency, with time, the benefit from muscle afferent attenuation is negated.